On a method for constructing the Green function of the Dirichlet problem for the Laplace equation - Kalmenov, T.Sh. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The study of boundary value problems for elliptic equations is of both theoretical and applied interest. A thorough study of model physical and spectral problems requires an explicit and effective representation of the problem solution. Integral representations of solutions of problems of differential equations are one of the main tools of mathematical physics. Currently, the integral representation of the Green function of classical problems for the Laplace equation for an arbitrary domain is obtained only in a two-dimensional domain by the Riemann conformal mapping method. Starting from the three-dimensional case, these classical problems are solved only for spherical sectors and for the regions lying between the faces of the hyperplane. The problem of constructing integral representations of general boundary value problems and studying their spectral problems remains relevant. In this work, using the boundary condition of the Newtonian (volume) potential and the spectral property of the potential of a simple layer, the Green function of the Dirichlet problem for the Laplace equation was constructed.
Лаплас теңдеуі үшін Дирихле есебінің Грин функциясының интегралдық көрсетілімі туралы
Об интегральном представлении функции Грина задачи Дирихле для уравнения Лапласа
Keywords: Laplace equation; Green function; Dirichlet problem; simple layer potential